Diseases don't need passports: A life course approach to understanding high-risk sexual behaviors and attitudes among international travelers. Issue 6 (17th August 2020) - Paat, Yok-Fong; Torres, Luis R.
ABSTRACT: International travelers, who consist of a large proportion of the U.S. population, play a critical role in sustaining public health and homeland security. This study examined the life course and contextual factors that increased propensities for high-risk sexual behaviors and attitudes among international travelers. Forty-five frequent international travelers were recruited through purposive sampling to participate in an in-depth semi-structured interview to understand factors facilitating transmission of sexual health risks. Contrary to many quantitatively oriented travel and public health studies, this study was able to capture rich information (e.g., emotions, thought processing, decision-making process, context of risk) not easily available through traditional quantitative method of data collection (e.g., survey). Overall, study findings show that life transitions, factors weakening social control or self-control, and strengthening anonymity can promote a context that increases sexual exchanges between locals and travelers while abroad. This research calls for more public health, epidemiological, and social behavioral data that better depict the vulnerability that international travelers confront.